조경설계공모의 문제점 및 요소별 중요도 분석 - 이주희; Joo Hee Lee; 조세환; Se Hwan Cho (한국조경학회지, 2013)
본 연구는 현재 조경 설계공모 과정에서 발생되고 있는 문제점을 AHP 기법을 활용하여 분석 및 고찰함으로써 조경설계 공모제도 개선을 위한 기초자료 제시를 목적으로 수행하였다. 본 연구 결과, 첫째, 조경설계공모 제도의 문제점을 이루고 있는 1계층 항목에서는 ‘당선작 선정과정’이 가장 중요한 문제점으로 나타났고, 그 뒤를 따라 ‘당선작 이후 설계변화’, ‘조경설계 공모 지침’, ‘조경설계 공모 방식’ 순으로 중요도가 나타났다. 둘째, 계층 1을 구성하고 있는 하위 항목에서는 ‘비 조경전문가의 심사 참여’가 가장 심각한 문제로 의견이 모아졌으며, ‘심사위원의 전문성 결여’, ‘심사배점방식의 문제’ 항목 등 ‘당선작 선정과정’에 해당하는 하위 요소가 전체 12개의 요소 중 가장 높은 순위를 차지하고 있는 것으로 나타났다. 또한 조경설계공모 당선이 이루어진 후에 일어나는 ‘발주자의 임의 설계변경 현상’에 대한 중요도도 높게 나타남으로써 조경설계공모의 문제점에서 간과할 수 없는 사항으로 분석되었다. 본 연구는 조경설계공모상 과정에서 발생하는 문제점의 우선순위를 선정함으로써 향후 제도 개선 시 선행적으로 검토가 이루어져야 할 부분을 찾았다는 점에 의의가 있었으며, 이러한 문제점을 근거로 향후 제도개선 방안에 대한 후속 연구가 있어야 할 것임이 제안되었다. This study is conducted for the purpose of analyzing and contemplating the problems with the competition in current landscape design, with the goal of improving the landscape design competition system by using the AHP technique. The result of this study, first describe the Landscape design competition system that formed the problems and show the most important problem followed by other problems shown in order of importance, which are ‘design changes after winning’, ‘Guidelines for design competition’ and ‘Landscape design competition manner’. Secondly, in the low rank article make up the level one -From a total 12 elements from the low rank article corresponding in ‘process of winner selection’ the ‘Unprofessional landscape participate the screening’ collected comments for the biggest problem, ‘lack of expertise in judgement’, ‘problems with the examination scoring system’ and other articles, the corresponding in ‘process of winner selection’ appears at the highest ranks. It also happens that after making the choice in the landscape design competition, the importance of ‘client`s design change symptoms’ appears high. As a result the overlooked details of the landscape design competition`s problems were analyzed. This study has prioritized the problems by problems which landscape design competition institutions most frequently have. Based on this ranking, there is significance purpose to create proactive system improvements in the future. By analyzing these problems, we will be better able to develop improvements to the future system.